PENGEMBANGAN EDUKASI BERBASIS KONSELING UNTUK MENGURANGI GANGGUAN POLA MENSTRUASI PADA AKSEPTOR IMPLANT - Joeliatin; Binti Asrofin (Rena Cipta Mandiri, 2026)
The use of implant contraception may cause side effects such as menstrual cycle disturbances, including spotting, amenorrhea, and irregular bleeding. Counseling-based education is needed to improve acceptors’ understanding in managing these side effects. This study aims to determine the effect of counseling-based education on menstrual cycle disturbances among implant contraceptive acceptors. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 implant contraceptive acceptors selected using a purposive sampling technique. The intervention was carried out through counseling-based education, and measurements were taken using questionnaires before (pretest) and after (posttest) the intervention. Data analysis was performed using a paired t-test with a significance level of 0.05. The results showed that the mean score of menstrual cycle disturbances before the intervention was 79.03 and decreased to 66.70 after the intervention. The paired t-test results obtained a t-value of 89.108 with a p-value of 0.000 (p < 0.05), indicating a significant effect of counseling-based education on reducing menstrual cycle disturbances among implant acceptors. Counseling-based education was proven to be effective in reducing menstrual cycle disturbances among implant contraceptive acceptors.